2020
DOI: 10.3389/fphar.2020.00204
|View full text |Cite
|
Sign up to set email alerts
|

Purmorphamine Attenuates Neuro-Inflammation and Synaptic Impairments After Hypoxic-Ischemic Injury in Neonatal Mice via Shh Signaling

Abstract: Purmorphamine (PUR), an agonist of the Smoothened (Smo) receptor, has been shown to function as a neuroprotectant in acute experimental ischemic stroke. Its role in hypoxic-ischemic (HI) brain injury in neonatal mice remains unknown. Here we show that PUR attenuated acute brain injury, with a decrease in Bax/Bcl-2 ratio as well as inhibition of caspase-3 activation. These beneficial effects of PUR were associated with suppressing neuro-inflammation and oxidative stress. PUR exerted long-term protective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…There is one report showing that expressions of Shh, Gli-1, and Ptch1 protein were all upregulated in cortical neurons at 6 h after MACO injury in rats [ 10 ], while others have reported that Gli1 and Ptch1 expressions were upregulated at 6, 12, 24, and 48 h postischemic injury [ 20 ]. However, a downregulation of Shh expression within the cortex has also been reported in the early stages after experimental subarachnoid hemorrhage [ 11 , 21 ] and hypoxia-ischemia in neonatal mice [ 12 ]. In the present study, we found that neuronal expressions of Shh and Gli-1 were increased in the early stages of OGD insult, while the expressions of Shh, Gli-1, and Ptch were decreased at later time points following OGD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is one report showing that expressions of Shh, Gli-1, and Ptch1 protein were all upregulated in cortical neurons at 6 h after MACO injury in rats [ 10 ], while others have reported that Gli1 and Ptch1 expressions were upregulated at 6, 12, 24, and 48 h postischemic injury [ 20 ]. However, a downregulation of Shh expression within the cortex has also been reported in the early stages after experimental subarachnoid hemorrhage [ 11 , 21 ] and hypoxia-ischemia in neonatal mice [ 12 ]. In the present study, we found that neuronal expressions of Shh and Gli-1 were increased in the early stages of OGD insult, while the expressions of Shh, Gli-1, and Ptch were decreased at later time points following OGD.…”
Section: Discussionmentioning
confidence: 99%
“…PUR, which has also been shown to promote blood-brain barrier formation, plays a crucial role in activation of the endogenous anti-inflammatory system within the CNS [ 9 ], and recent findings have indicated that PUR protects cortical neurons and restores neurological deficits after ischemic stroke in rats [ 10 ]. It has been reported by us that PUR exerted neuroprotection against subarachnoid hemorrhage-induced injury in adult rats [ 11 ] and hypoxia-ischemia in neonatal mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sonic hedgehog (SHH) signaling pathway is essential for the maintenance of integrity and immune homeostasis of the BBB ( 126 ). Agonists of SHH, such as purmorphamine, a compound that activates the SHH by promoting smoothened protein ( 127 ), reduce BBB damage in animal models of infection and ischemic stroke ( 128 – 130 ). Although little evidence exists of the safety of purmorphamine in humans, this agent warrants further exploration for the management of neurotoxicity associated with severe infections, including COVID-19.…”
Section: Potential Therapeutics For the Neurological Complications Ofmentioning
confidence: 99%
“…High expression of SHH was observed in gingival crevicular fluid of patients with periodontitis [12], indicating that SHH may participate in the inflammatory response of periodontitis. Multiple studies have shown that the SHH signaling pathway can inhibit the production of inflammation in disease and inhibit cell apoptosis, moreover, SHH signaling pathway plays an important role in cell differentiation and regeneration [13][14][15].…”
Section: Introductionmentioning
confidence: 99%